0262 Sleep-wake cycle circadian disruption after chronic alcohol intake in a rat model of anxiety. (25th May 2022) - Fierro, Adriela; Cortés, Carmen; Eguibar, José
Abstract: Introduction: Alcohol intake can produce disruptions in sleep-wake cycle, including circadian alterations like phase shifts. Alcohol intake is increased in subjects with anxiety to diminish its symptoms. We have selectively bred two sublines from Sprague-Dawley rats that differs on its yawning frequency. The high-yawning (HY) rats have a mean of 20 yawns/h, whereas the low-yawning (LY) rats have only 2 yawns/hour. LY male rats had high anxiety-like behavior in standardized tests and high preference for alcohol intake. The aim of this study was to assess circadian disruption of sleep-wake cycle after chronic alcohol consumption. Methods: We used 8 male rats from HY and LY at 3 months of age. All rats were kept in acrylic boxes with food pellets and purified water ad libitum under a light-dark cycle of 12:12 (lights on at 0700) and temperature of 21 ± 1 °C. All subjects were implanted for EEG, EMG and EOG recordings to characterize sleep-wake phases. A basal sleep-wake recording was obtained for 24 h. A second and third recording were made after a 7 days of alcohol administration as a single source of hydration (AL1) and a 3 week two-bottle choice alcohol preference protocol (AL2) were carried out. We used COSINOR analysis to determine phase and cycle alterations of sleep-wake circadian rhythm of all subjects. Results: After alcohol intake, there was a significant difference only in the acrophases of awake periods (P<0.01) and slow wave sleep (SWS, P<0.001) in both AL1 and AL2 conditions for the HY subline, with a phase delay of 90 min for awake, 30 min for SWS and an advanced phase of 40 min for rapid eye movement sleep (REM) with respect to basal condition. In the case of LY subline, there was a significant difference only in SWS (P<0.001) and REM sleep (P<0.05) acrophases for both AL1 and AL2 conditions, with a phase delay of 7 h for wake, 40 min for SWS and 1 h for REM sleep. Conclusion: It has been reported that alcohol disrupt circadian synchronization of the sleep-wake cycle, producing a general delay of SWS and REM sleep phases. Additionally, subjects with basal circadian disruptions are more susceptible to increase their intake of alcohol and other addictive drugs. So, LY male rats are an adequate model for higher susceptibility to alcohol intake. Support (If Any): Partially supported by PRONACES-CONACYT grant and VIEP-BUAP 2021 to CA in Neuroendocrinología (BUAP-CA-288). AFR is PhD on Physiological Sciences fellowship from CONACYT No. 926368